2022
DOI: 10.21203/rs.3.rs-1542801/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CyberKnife Xsight versus Fiducial-based Target-tracking: A Novel 3D Dosimetric Comparison in a Dynamic Phantom

Abstract: Background: The CyberKnife Xsight lung-tracking system (XLTS) provides an alternative to fiducial-based target-tracking systems (FTTS) for non-small-cell lung cancer (NSCLC) patients without invasive fiducial insertion procedures. This study provides a method for 3D independent dosimetric verification of the accuracy of the FTTS compared to the XLTS without relying on log-files generated by the CyberKnife system. Methods: A respiratory motion trace was taken from a 4D-CT of a real lung cancer patient and appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In general, error assessment is necessary for the CK to study the impact of delivery uncertainties and select appropriate PTV margins. In this context, a review of previous studies reveals several sources of error 7–17 . Nakayama et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, error assessment is necessary for the CK to study the impact of delivery uncertainties and select appropriate PTV margins. In this context, a review of previous studies reveals several sources of error 7–17 . Nakayama et al.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a review of previous studies reveals several sources of error. [7][8][9][10][11][12][13][14][15][16][17] Nakayama et al and Descovich et al found that the PTV margin estimation requires the consideration of STRS modeling and prediction errors. 7,9 According to Yang et al study, the CK system has five main sources of error.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation